2010
DOI: 10.1061/(asce)ps.1949-1204.0000041
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Buried Flexible Pipe-Soil Systems

Abstract: Reliability analysis of the buried flexible pipe-soil system is performed from three different failure criteria: ͑1͒ deflection; ͑2͒ buckling; and ͑3͒ wall thrust. The response surface methodology is used to establish approximate functional relationships between input variables and output responses and reliability analysis is performed using first-order reliability method approach. The available analytical solutions as well as the results of the numerical analysis are used in the reliability analysis and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Considering the failure probability of 0.1 (10%) as a threshold level for the safe service life (Babu and Srivastava, 2010), the study illustrates that the safe service life in the worst case scenario is about 50 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the failure probability of 0.1 (10%) as a threshold level for the safe service life (Babu and Srivastava, 2010), the study illustrates that the safe service life in the worst case scenario is about 50 years.…”
Section: Resultsmentioning
confidence: 99%
“…Buckling is a premature failure in which the pipe is not able to maintain its initial circular shape and the structure becomes unstable at a stress level that is well below the yield strength of the structural material (Sivakumar Babu and Srivastava, 2010). The actual buckling pressure should be less than the critical buckling pressure for the safety of structure.…”
Section: Buckling Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, system reliability analysis has gained increasing attention in geotechnical engineering (Babu & Srivastava, 2010;Basha & Babu, 2010;Jiang et al, 2014;Li, Jiang, Chen, & Zhou, 2011;Li, Phoon, Wu, Chen, & Zhou, 2013;Li, Zhou, Lu, & Jiang, 2009;Low et al, 2011). Li et al (2009) analysed the system reliability for evaluating the stabilities of rock wedges using an Ndimensional equivalent method, which demonstrated that the probability of failure would be overestimated if the correlations between different failure modes of the wedge were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2009) analysed the system reliability for evaluating the stabilities of rock wedges using an Ndimensional equivalent method, which demonstrated that the probability of failure would be overestimated if the correlations between different failure modes of the wedge were not considered. Babu and Srivastava (2010) employed response surface methodology to calculate the reliability indices of a buried flexible pipe-soil system from three different failure criteria. Basha and Babu (2010) analysed the soil uncertainties associated with horizontal seismic acceleration and surcharge load in the seismic analysis of geosynthetic reinforced soil walls under three failure modes.…”
Section: Introductionmentioning
confidence: 99%